X-ray absorption near edge spectroscopy of thermochromic phase transition in CuMoO4 - Jonane, I.; Cintins, A.; Kalinko, A.; Chernikov, R.; Kuzmin, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
Thermochromic phase transition was studied in CuMoO4 using the Cu and Mo K-edge x-ray absorption spectroscopy in the temperature range of 10–300 K. The hysteretic behavior has been evidenced from the temperature dependence of the pre-edge shoulder intensity at the Mo K-edge, indicating that the transition from brownish-red γ-CuMoO4 to green α-CuMoO4 occurs in the temperature range of 230–280 K upon heating, whereas the α-to-γ transition occurs between 200 and 120 K upon cooling. Such behavior of the pre-edge shoulder at the Mo K-edge correlates with the change of molybdenum coordination between distorted tetrahedral in α-CuMoO4 and distorted octahedral in γ-CuMoO4. This result has been supported by ab initio full-multiple-scattering x-ray absorption near edge structure (XANES) calculations.